Study of the effect of the method of applying cryoprotectors on the preservation of Mentha longifolia seed material during cryopreservation - Dodonova, A.Sh.; Antipova, D.D. (Fundamental and Experimental Biology, 2024)
This article is devoted to optimizing the conditions for cryopreservation of seed material of Mentha longifolia. Mentha longifolia is an essential oil plant that is actively used in the perfumery, pharmaceutical and food industries. The cryopreservation experiments use the following endocellular and exocellular cryoprotectants: polyvinylpyrrolidone (PVP), glycerol, and dimethysulfoxide (DMSO). In addition, we study the effect of the growth characteristics of seeds on the preservation during cryopreservation of the method of applying a cryoprotectant: at room temperature and in an ice bath. The initial germination of long-leaved mint seeds is 76.3±2 %, and the germination energy is 70.3±1.8 %. When frozen in liquid nitrogen without the use of cryoprotectants, the germination rate was 64.9±0.8 %, and the germination energy was 18.95±0.2 %. It should be noted that the germination energy indicator turned out to be sensitive to the deposition of seed material at extremely low temperatures. An analysis of the results of maintaining the viability of long-leaved mint seeds when they are frozen in cryoprotectants of various compositions in the case of their introduction at room temperature indicates that the tendency for a sharp decrease in germination energy is observed in all variants of the experiment. The best options for cryoprotectants to preserve the growth characteristics of the seed material are DMSO 2.5 % and PVP 3 % applied in an ice bath. The germination of seeds stored in these cryoprotectants is 85.8±3.1 % and 87.6±2.3 %, respectively. Thus, it is found that the best way to apply cryoprotectants during cryopreservation of long-leaved mint seeds is a temperature close to 0 °C; in this case, both germination and seed germination energy are seriously increased.